Safe hospital preparedness in the era of COVID-19: The Swiss cheese model (2020)
Since it first emerged in December 2019, coronavirus disease 2019 (COVID-19) has spread rapidly worldwide. During the pandemic of an emerging infectious disease, it is very important to prevent nosocomial outbreaks and operate hospitals safely to maintain their functions. In this article, we present the strategies for safe hospital operations based on the experiences of the Republic of Korea early in the COVID-19 pandemic. Each hospital should maintain multiple layers of defenses to prevent even small cracks in the hospital’s quarantine system.